2018
DOI: 10.1037/pha0000158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Methyl-D-aspartate (NMDA) antagonists ketamine, methoxetamine, and phencyclidine on the odor span test of working memory in rats.

Abstract: The glutamate hypothesis proposes that N-Methyl-D-aspartate (NMDA) receptor hypofunction underlies cognitive and perhaps other schizophrenic symptoms. The present study used the odor span task to assess the effects of NMDA antagonists on remembering multiple stimuli in rodents. This task uses an incrementing nonmatching-to-sample procedure in which responses to a new olfactory stimulus are reinforced on each trial, whereas responses to previously presented stimuli are not. NMDA antagonists have been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…In the successive arrangement, the proportion of responses to S+/S‐ is the critical measure. However, span can actually be a misleading measure in OST studies; unlike human working memory tasks such as the digit span, rats often perform with high accuracy after their first error (Galizio et al, 2013; 2016; Mathews et al, 2018). In sum, the absence of a span measure should not be viewed as a liability of the successive incrementing NMTS procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the successive arrangement, the proportion of responses to S+/S‐ is the critical measure. However, span can actually be a misleading measure in OST studies; unlike human working memory tasks such as the digit span, rats often perform with high accuracy after their first error (Galizio et al, 2013; 2016; Mathews et al, 2018). In sum, the absence of a span measure should not be viewed as a liability of the successive incrementing NMTS procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The OST has become widely used in behavioral pharmacology and neuroscience and, following the interpretation of Dudchenko et al (2000), is often represented as providing a rodent model of working memory capacity (e.g., Bratch et al, 2016; Cui et al, 2011; Davies et al, 2017; DeFalco et al, 2019; Rushforth et al, 2010; 2011; Young et al, 2007). In support of this interpretation are findings that accuracy declines as the number of odors to remember increases and that this decline occurs even when the number of comparison choices is held constant across the session (Galizio et al, 2013; MacQueen et al, 2011; Mathews et al, 2018). Indeed, the OST has been considered to be a benchmark procedure to study working memory capacity in rodents by the CNTRICS group (Cognitive Neuroscience Treatment Research to Improve Cognition in Schizophrenia) and may be useful as a model for a variety of pathologies (Dudchenko et al, 2013; MacQueen et al, 2018).…”
mentioning
confidence: 94%
“…Drug resistance remains an obstacle in cancer treatment. Though multiple mechanisms underlying drug resistance in cancers, such as improved DNA repair capacity, 1 defects in the DNA damage response, 2,3 anti-apoptosis, 4 pro-migration, 5 pro-proliferation effects, 6 autophagy, 7 tumor-associated compensatory pathways, 8 and changes in drug transport, 9 have been proposed, the exact mechanism of drug resistance in cancer is highly complex and has not been fully understood yet. Therefore, discoveries of new drug sensitivity-associated targets and effective drug combinations are considered as effective and promising strategies for improving the survival rate of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these effects generally depend on the number of stimuli to remember. That is, effects were minimal when the memory load was low, but impairment of accuracy accelerated as the number of odors to remember increased during the session (Galizio et al, 2013;MacQueen et al, 2011;Mathews et al, 2018). In summary, findings from multiple laboratories have converged to find that NMDA antagonists interfere with memory capacity in the OST.…”
mentioning
confidence: 96%
“…In early work from our laboratory, we found that the noncompetitive NMDA antagonist dizocilpine/MK-801 (DZP) impaired span length and overall OST accuracy at doses that had no effect on a simple discrimination task that controlled for drug effects on sensorimotor function, motivation, and reference memory (Galizio et al, 2013;MacQueen et al, 2011). More recently we found that two additional non-competitive NMDA antagonists, phencyclidine (PCP) and methoxetamine (MXE), selectively impaired OST accuracy, although the low-efficacy NMDA antagonist ketamine was less selective (Galizio et al, 2016;Mathews, Mead, & Galizio, 2018). Other laboratories have shown that the competitive NMDA antagonist 3-(2-carboxypiperazin-4-yl) propyl-1-phosphonic acid (CPP) produced effects that were similarly selective to OST performance, as did the GluN2B-selective antagonist Ro 256981 (Davies et al, 2013(Davies et al, , 2017MacQueen, Dalrymple, Drobes & Diamond, 2016).…”
mentioning
confidence: 99%